2000
DOI: 10.1080/016502500383287
|View full text |Cite
|
Sign up to set email alerts
|

Visual filtering and covert orienting in persons with Down syndrome

Abstract: A forced-choice reaction time (RT) task was used to examine the relations between covert orienting (shifts of visual attention independent of eye movement) and filtering (the mhlbition of processing of melevant stllnu11) components of attention in pers'Jns with Down syndrome (n = 17} and children of average intelligence (n = 17) matched for mental age (MA), (MA = approximately 5 years). Conditions varied with regard ta presence or absl.::nce of distractors\ and the validity (valid, invalid, or neutraI) of loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…This transform is undefined if P = 1 or 0, which occurred in three cases which were subsequently excluded from analyses. K‐BIT raw scores were converted to standard scores from which an approximate mental age was obtained (Randolph & Burack, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This transform is undefined if P = 1 or 0, which occurred in three cases which were subsequently excluded from analyses. K‐BIT raw scores were converted to standard scores from which an approximate mental age was obtained (Randolph & Burack, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The sample comprised 16 males and 11 females, with an average standard score of 66.04 and mean mental age of 6.71 years, assessed using the matrices subtest of the Kaufman Brief Intelligence Test (K‐BIT) (Kaufman & Kaufman, 1990). This measure has been used previously to obtain an approximate measure of non‐verbal mental age in research involving participants with DS (Randolph & Burack, 2000). Characteristics of the two groups are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Although there has been considerable research about possible mechanisms underlying the verbal impairment, it is not clear which are the factors underlying the (controversial) visual‐spatial relative strength. Preserved visual‐attentional abilities (Iarocci & Burack 1998; Randolph & Burack 2000; Goldman et al. 2005) and good spatial abilities (Laws 2002) are some of the possible underpinnings; however, the evidence supporting each of these proposals is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…There also may be other aspects of executive functioning that underlie developmental improvement on rule-based category learning tasks (e.g., set-shifting), though we are aware of no studies that have demonstrated this specifically. Several studies have shown that children and adults with DS perform below their developmental level on a variety of tasks measuring inhibition (e.g., Atkinson & Braddock, 2012; Borella, Carretta, & Lanfranchi, 2013; Kogan et al, 2002; Lanfranchi, Jerman, Dal Pont, Alberti, & Vianello, 2010; Rowe, Lavender, & Turk, 2006; Wilding, Cornish, & Munir, 2002; but see Carney, Brown, & Henry, 2013; Lee et al, 2011; Pennington, Moon, Edgin, Stedron, & Nadel, 2003; Randolf & Burack, 2000) and working memory (e.g., Carney et al, 2013; Lanfranchi, Cornoldi, & Vianello, 2004; Lanfranchi, Jerman, & Vianello, 2009; Lanfranchi et al, 2010; Munir, Cornish, & Wilding, 2000; Vicari, Carlesimo, & Caltagirone, 1995; but see Edgin, Pennington, & Mervis, 2010). Although few studies have examined set-shifting directly in DS, some evidence points to special difficulty in this skill (Carney et al, 2013; Lanfranchi et al, 2010; Rowe et al, 2006).…”
mentioning
confidence: 99%